Efeito do uso tópico de capsaicina na mucosite intestinal induzida por 5-fluorouracil em camundongos Swiss - Lorrayne Gonçalves Lopes (2014)
5-FU (5-Fluorouracil) is a key chemotherapeutic agent in the tratament of various cancer, being widely used against colorectal cancer. Intestinal mucositis has adverse effect such as diarrheia and vomiting that often limit the therapy affects the quality of life of pacients as well as the treatment continuity. Capsaicin (trans-8-methyl-N-vanillyl-6- nonenamide) is a component of various kinds of pepper and responsible for their pungency. It presents various pharmacological effects, including anti-inflammatory effects even when applied directly to the skin. In the present study, we evaluated the preventive effects of topical capsaicin to 0,075% or placebo (vehicle without capsaicin) in mice with intestinal mucositis induced by 5-FU. For this, the creams were administrared topically on the dorsum of the animals for seven days prior to intraperitoneal administration of 5-FU (200mg/kg weight). Alterations of body weight, food and water intake in the fisrt and last day of capsaicin application and at the end of the experiment (three days of administration of 5-FU) were evaluated. The animals were euthanized to evaluate the morphology of the intestinal mucosal, histopathological score, inflammatory infiltrate, cytokine profile, oxidative stress and intestinal permeability were assessed. In animals of placebo group receiving 5-FU, the mucositis was confirmed by the weight loss, mucosal lesions more severe, mucosal thickening and cell loss. The increased activity of MPO and EPO enzymes, indicating greater infiltration of neutrophils and eosinophils, respectively, and increased production of TNF were also seen. Were also observed higher levels of IL-10 in animals with mucositis and placebo, indicating a potential compensatory mechanism to conteur the inflammation. The pretreatment with capsaicin attenuated the cytotoxic effects of 5-FU. In the capsaicin group, was found an improvement of morphological architecture and mucosal integrity as demonstrated by higher villus height. There was also a reduction in the inflammatory profile, with reduction of inflammatory cells infiltration, lower concentrations of TNF and lower oxidative stress, as suggested by the lower activity of SOD and hydroperoxide concentration. No differences were observed in terms of intestinal permeability. In conclusion, the results shows that topical application of capsaicin is able to reduce inflammation and oxidative stress caused by 5-FU.